Can a bleaching toothpaste containing Blue Covarine demonstrate the same bleaching as conventional techniques? An in vitro, randomized and blinded study - Andréa Abi Rached DANTAS; Janaina Freitas BORTOLATTO; Ávery RONCOLATO; Hugo MERCHAN; Michael Christopher FLOROS; Milton Carlos KUGA; Osmir Batista de OLIVEIRA JUNIOR (University of São Paulo, 2015)
ABSTRACT Objective The purpose of this in vitro study was to compare the efficacy of a bleaching toothpaste containing Blue Covarine vs. conventional tooth bleaching techniques using peroxides (both in-office and at-home). Material and Methods Samples were randomly distributed into five experimental groups (n=15): C - Control; BC - Bleaching toothpaste containing Blue Covarine; WBC - Bleaching toothpaste without Blue Covarine; HP35 - In-office bleaching using 35% hydrogen peroxide; and CP10 - At-home bleaching with 10% carbamide peroxide. The dental bleaching efficacy was determined by the color difference (ΔE), luminosity (ΔL), green-red axis (Δa), and blue-yellow axis (Δb). The CIELab coordinates were recorded with reflectance spectroscopy at different times: T0 - baseline, T1 - immediately after bleaching, T2 - 7 days, T3 - 14 days, and T4 - 21 days after the end of treatments. Data were analyzed by a repeated measures mixed ANOVA and post hoc Bonferroni test, with a significance level of 5%. Results No significant differences were found between the treatment groups C, BC, and WBC. The groups HP35 and CP10 showed significantly higher whitening efficacy than groups C, BC, and WBC. Conclusions There were no significant differences in the whitening efficacy between a Blue Covarine containing toothpaste, a standard whitening toothpaste, and a control. Neither of the whitening toothpastes tested were as effective as in-office or at-home bleaching treatments.